2018
DOI: 10.5194/esurf-6-101-2018
|View full text |Cite
|
Sign up to set email alerts
|

Optimising 4-D surface change detection: an approach for capturing rockfall magnitude–frequency

Abstract: Abstract. We present a monitoring technique tailored to analysing change from near-continuously collected, high-resolution 3-D data. Our aim is to fully characterise geomorphological change typified by an event magnitude-frequency relationship that adheres to an inverse power law or similar. While recent advances in monitoring have enabled changes in volume across more than 7 orders of magnitude to be captured, event frequency is commonly assumed to be interchangeable with the time-averaged event numbers betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
146
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 127 publications
(170 citation statements)
references
References 84 publications
(114 reference statements)
8
146
0
Order By: Relevance
“…Such discontinuities isolate the landslide mass from the rest of the slope. For example, Williams et al (2018) showed a rollover in frequency-size distribution of rock-falls if mapping is conducted using a low temporal resolution. Even in this situation, however, landslide margins are likely to produce smaller, continuing failures as the disturbed topography seeks equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such discontinuities isolate the landslide mass from the rest of the slope. For example, Williams et al (2018) showed a rollover in frequency-size distribution of rock-falls if mapping is conducted using a low temporal resolution. Even in this situation, however, landslide margins are likely to produce smaller, continuing failures as the disturbed topography seeks equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is only one case study supporting this argument by monitoring rock-falls on a slope (Williams et al, 2018). However, there is only one case study supporting this argument by monitoring rock-falls on a slope (Williams et al, 2018).…”
Section: Proposed Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations